Alternative ground cover in lettuce production under tropical climate conditions - Moura, Ernandes Guedes; Silva, Fábio de Sousa; Silva, Rodrigo Fonseca da; Andrade, Fabrício Ribeiro; Silva, Jodean Alves da; Silva, Ana Teresa Pereira da (Revista Agrogeoambiental, 2019)
Alternative farming techniques to increase lettuce quality and productivity, rising environmental and social development has been the subject of several studies. The objective of this study was to select economic and readily available cover materials to enhance the production of curly lettuce, in the south of Piauí. It was used a Randomized Block Design with four replications, with the following ground cover treatments: rice husk (Oryza sativa L.), chopped andropogon straw grass (Andropogon gayanus Kunth), sawmill dust and a control without ground cover. The andropogon straw grass can be recommended in lettuce production under the prevailing edaphoclimatic conditions at Uruçuí in southwest Piauí.